RANCANG BANGUN PENDETEKSI SERANGAN DEAUTHENTICATION PADA JARINGAN WIFI BERBASIS ESP8266 - Nurbayazi, Muhamad; Mardiansyah, Ahmad Zafrullah; Zubaidi, Ariyan (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
In the modern era that is so tied to the internet, network security is important because the internet is basicallyinsecure. To connect to an internet network, you can use a wireless network that uses an access point to transmitsignals from WiFi. By using WiFi, users can enjoy communication at home, in the office or while traveling withouthaving to bother using cables, but there are drawbacks to this benefit. Because wifi communications occur over the air, they can be intercepted easily. A relatively easy attack on a WiFi network is a deauthentication attack. Adeauthentication attack is an attack that occurs because too many deauthentication messages are sent. Thisdeauthentication message can be sent by the user's device or access point to notify the receiving device that theircommunications should be terminated. Apart from causing communication disruption between connected devices, deauthentication attacks are also the beginning of other follow-up attacks, one of which is the evil twin attack. To prevent further attacks, a deauthentication attack detection tool is needed so that by detecting deauthentication attacks, users or admins can take preventive and security measures against the WiFi network. This research aims to improve network security, especially WiFi networks, by designing and building a tool that detects and provides warnings when deauthentication attacks occur in the form of visual and audio warnings to WiFi users, both users and admins, by utilizing buzzers and LEDs as well as notifications via the Telegram application so that they can Minimize the occurrence of deauthentication attacks on ESP8266 NodeMCU based WiFi networks. Based on tool testing on 10 access point samples, the tool's percentage of success in detecting deauthentication attacks is 100%